Penerapan Model Pembelajaran Team Assisted Individualization Untuk Meningkatkan Hasil Belajar Tematik Terpadu Kelas VI MIS Juhari Imi - Marwiyah Marwiyah; Regina Fredika Sipayung (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This class action research intends to improve student learning outcomes with the Team Assisted Individualisation learning model in class VI MIS Juhari Ilmi with a qualitative and quantitative approach. The results showed an increase in the first cycle lesson plan with an average of 84.72% good achievement, increasing in cycle II to 94.44% very good achievement. The implementation of learning in the teacher aspect of cycle I obtained an average of 84.09% good achievement and cycle II was 95.45% very good achievement, while the implementation of learning in the student aspect obtained an average of 81.81% good achievement and in cycle II obtained an average of 95.45% very good achievement. Student learning outcomes in cycle I obtained an average score of 77.38 sufficient achievements and increased in cycle II to 87.49 good achievements. So it can be concluded that the Team Assisted Individualization learning model can improve student learning outcomes in integrated thematic learning.